HUBUNGAN SIKAP KARYAWAN STIKES AUFA ROYHAN DENGAN PENGGUNAAN KANTONG PLASTIK - Nurul Hidayah Nasution; Yanna Wari Harahap (Parapemikir : Jurnal Ilmiah Farmasi, 2019)
The use of plastic bags as a place to store goods is a cause of environmental damage and pollution. Health behavior for humans can be seen from the behavior of their environmental health, environmental health behavior is included in health protection for humans, one of which includes behavior towards waste and its management (Notoatmodjo, 2013). STIKES Aufa Royhan with the use of plastic bags. This type of research is analytical research with cross sectional research design. Research conducted at the Aufa Royhan STIKes in Padangsidimpuan City in February - July 2018. The population of this study were all employees at the Aufa Royhan STIKes in Padangsidimpuan City with a sample of 38 people. The independent variable in this study is the temporary employee variable, the dependent variable is the use of plastic bags. Univariate and bivariate data analysis. The results obtained from the Aufa STIkes company have a negative attitude of 84.2% and a positive relationship with attitudes (p = 0.018 and r = 0.385) with the use of plastic bags and have an adequate increase in positive direction which will increase the company's endurance so that many employees have bad actions in using plastic bags. Suggested to respondents to be able to improve positive attitudes by getting information through various media both oral and writtenKeywords:. Attitude, plastic